2013
DOI: 10.1039/c3dt51364e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CeO2 morphology on the catalytic activity of CeO2–Pt hybrids for CO oxidation

Abstract: Ceria, because of its excellent redox behavior and oxygen storage capacity, is used as a catalyst for several technologically important reactions. In the present study, different morphologies of nano-CeO2 (rods, cubes, octahedra) were synthesized using the hydrothermal route. An ultrafast microwave-assisted method was used to efficiently attach Pt particles to the CeO2 polyhedra. These nanohybrids were tested as catalysts for the CO oxidation reaction. The CeO2/Pt catalyst with nanorods as the support was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 71 publications
(88 reference statements)
2
58
0
Order By: Relevance
“…The enhanced activity is attributed to the increased bonding strength between the Ni metal particles with the ceria support ( Figure 8), as well as an increase in the presence and transfer of lattice oxygen from the ceria support to metal particles [97]. Similar findings were also reported for Pt-and Pd-loaded ceria nanoshapes [98,99].…”
Section: Recent Work On the Structure And Reactivity Of Ceria Nanoshapessupporting
confidence: 81%
See 1 more Smart Citation
“…The enhanced activity is attributed to the increased bonding strength between the Ni metal particles with the ceria support ( Figure 8), as well as an increase in the presence and transfer of lattice oxygen from the ceria support to metal particles [97]. Similar findings were also reported for Pt-and Pd-loaded ceria nanoshapes [98,99].…”
Section: Recent Work On the Structure And Reactivity Of Ceria Nanoshapessupporting
confidence: 81%
“…papers that ceria rods have exposed (100) and (110) surfaces and grow along the {110} direction has been significantly relied on during the past eight years for furthering the field [19,21,76,92,96,[98][99][100]102,104,[106][107][108]. However, discrepancies in the literature do exist.…”
Section: Figurementioning
confidence: 99%
“…In Fig. 3e and f, the O 1s spectra can be fitted into two peaks at 529.4 eV and 531.4 eV, in which the former should be indexed to lattice oxygen while the latter should be attributed to the chemisorbed oxygen species [46]. By comparing the peak areas of O 1s in CdS@CeO 2 -90 and CdS@CeO 2 -180, it can be found that the content of oxygen corresponding to the chemisorbed oxygen species in CdS@CeO 2 -180 is obviously higher than that in CdS@CeO 2 -90.…”
Section: Chemical Composition and Surface Propertymentioning
confidence: 99%
“…monodentate, bidentate, tridentate, bridging, and chelating carbonates, carboxylates and carbonites. [17][18][19][20][21][22][23][24][25][26] In such cases the identification of the species and their adsorption sites is often assisted by density functional calculations. [25][26][27][28][29] In particular, interaction of CO molecules with planar CeO 2 (111), CeO 2 (110), and CeO 2 (100) surfaces 27 as well as CeO 2 particles 28 has been modelled by density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%